2009
DOI: 10.1039/b816236k
|View full text |Cite
|
Sign up to set email alerts
|

Levels of toxic and essential metals in maternal and umbilical cord blood from selected areas of South Africa—results of a pilot study

Abstract: This pilot study uses concentrations of metals in maternal and cord blood at delivery, in seven selected geographical areas of South Africa, to determine prenatal environmental exposure to toxic metals. Samples of maternal and cord whole blood were analysed for levels of cadmium, mercury, lead, manganese, cobalt, copper, zinc, arsenic and selenium. Levels of some measured metals differed by site, indicating different environmental pollution levels in the regions selected for the study. Mercury levels were elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 39 publications
6
51
0
Order By: Relevance
“…In the rural study cohort, Mn was also measured in the respective umbilical cord blood samples, and the Mn levels in cord bloods were found to be double those found in the respective maternal samples. These findings are in agreement with the outcomes of the pilot of this study and other investigations, except that no significant correlation was found between maternal and the respective cord blood Mn levels, as has been reported in other studies 12,30 . Some studies have found some correlation between maternal MnB levels and birth outcomes such as birth weight and head circumference; however, these correlations were not evident in the current study cohort 15.31 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the rural study cohort, Mn was also measured in the respective umbilical cord blood samples, and the Mn levels in cord bloods were found to be double those found in the respective maternal samples. These findings are in agreement with the outcomes of the pilot of this study and other investigations, except that no significant correlation was found between maternal and the respective cord blood Mn levels, as has been reported in other studies 12,30 . Some studies have found some correlation between maternal MnB levels and birth outcomes such as birth weight and head circumference; however, these correlations were not evident in the current study cohort 15.31 .…”
Section: Discussionsupporting
confidence: 94%
“…It has been shown that due to the active transport of Mn across the placenta, levels of Mn in cord blood are higher than those in the maternal blood at delivery [10][11][12][13] . Su et al…”
Section: Introductionmentioning
confidence: 99%
“…The questionnaire was based on that used in comparable studies [13,15], with additional questions and adjustments pertaining to the Argentinian context. The information collected included: maternal age, previous children and breastfeeding experiences, medical history (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…The Arctic Monitoring and Assessment Programme (AMAP) started in 1991 and currently all Arctic countries are members, namely: Canada, Denmark, Finland, Iceland, Norway, Russia, Sweden and USA [9–12]. Countries located in tropical and southern areas have joined more recently, including South Africa [8,13], Brazil [6,14], Vietnam [15] and Australia [16,17]. The extent of human exposure, as measured by biological contaminant concentrations, has not been adequately investigated in South America.…”
Section: Introductionmentioning
confidence: 99%
“…The sampled population who are non-miners demonstrated the prevalence heavy metal pollutions in Nigeria among ordinary people. In a similar study in South Africa, the extent of heavy metal pollution was demonstrated by determining the concentrations of heavy metals in maternal and umbilical cord blood from residents of selected areas (Rollin et al, 2009). Although levels of some measured metals differ by site indicating different environmental pollution levels, unacceptably high levels of mercury, cadmium, lead and selenium were found.…”
Section: Environmental Pollution and Human Exposure To Heavy Metals Imentioning
confidence: 99%